Characterization and identification of potential Lactic Acid Bacteria as biological control agent against Ralstonia syzygii subsp. celebesensis of the Banana Blood Disease - Michell Kah Ven Sam; Roslina Jawan; Khim Phin Chong, Khim Phin (Journal of Pure and Applied Microbiology, 2024)
Banana is one of the primary fruits cultivated in Malaysia and currently decimated by the emergence of a disease, known as banana blood disease (BBD) which caused by Ralstonia syzygii subsp. celebesensis (Rsc). The BBD has significantly affected the yield and profits of the worldwide banana industry. To date, various approaches including chemical and biological controls have been attempted to manage this disease but none of them succeed in controlling the disease. The uses of lactic acid bacteria (LAB) in managing plant diseases have been reported earlier but little information is available. Therefore, this project is designed to identify and investigate potential plant-associated LAB as biological control agent (BCA) against Rsc by using agar well diffusion method. The inhibition zones of each well were observed after 72h and the isolated LAB that showed inhibition zones were proceed for molecular characterization using PCR amplification followed by gel electrophoresis. The sequences were used for phylogenetic analysis. In addition, each of the potential LAB were used to identify their morphological characterizations and biochemical testing. Throughout the study, the highest inhibition zones of LAB from kimchi and fermented milk achieved a diameter of 21.30 mm and 28.70 mm, respectively. Kimchi isolates showed the highest similarity which is 97% as Lactiplantibacillus plantarum species. Among the fermented milk isolates, the highest similarity which is 98% identified as Lacticaseibacillus paracasei.